The forgotten face of Type 1 diabetes: A rare case of Mauriac syndrome in an adolescent male - Singh, Avi; Laraib, Mohd; SHARMA, DEEPAK; SRIVASTAVA, SAURABH (Indian Journal of Case Reports, 2026)
Mauriac syndrome is a rare but classical complication of poorly controlled type 1 diabetes mellitus (T1DM), characterized by growth retardation, delayed puberty, hepatomegaly, and delayed skeletal maturation. Although uncommon in the era of intensive insulin therapy, sporadic cases continue to be reported, particularly in resource-constrained settings. We report the case of an 18-year-old male with T1DM diagnosed at the age of six years who presented with severe growth retardation, delayed pubertal development, and hepatosplenomegaly. The patient had a history of prolonged suboptimal glycemic control during childhood and adolescence and was receiving a basal-bolus insulin regimen comprising regular insulin (4 units before each meal) and insulin glargine (8 units at bedtime). At presentation, glycemic control was relatively satisfactory, with glycated hemoglobin (HbA1c) of 8.0%. Clinical examination revealed short stature below the third percentile, Tanner stage II sexual maturation, hepatomegaly, and splenomegaly. Growth chart analysis demonstrated persistent growth failure, while radiographic assessment of the left hand, wrist, and elbow revealed marked delay in skeletal maturation with a bone age of approximately nine years despite a chronological age of eighteen years. Endocrine evaluation showed low serum testosterone levels with inappropriately low gonadotropins, suggestive of hypogonadotropic hypogonadism. Ultrasonography confirmed hepatosplenomegaly, likely secondary to glycogenic hepatopathy. The constellation of long-standing T1DM, severe growth retardation, delayed puberty, delayed bone age, and hepatosplenomegaly established the diagnosis of classical Mauriac syndrome. This case highlights that Mauriac syndrome, though rare, remains an important differential diagnosis in adolescents with T1DM presenting with growth failure and delayed puberty, even in the presence of apparently acceptable contemporary glycemic control.